Me Too? The Invisible Older Victims of Sexual Violence - Lowenstein Lazar, Ruthy (2020)
A review of legal research on violence against women and elder abuse reveals a disturbing picture. There is hardly any American legal research examining sexual abuse of older women and its conceptualization in legal literature and treatment in the legal system. This Article attempts to fill the abovementioned gap and to bring the hidden issue of sexual violence against older women to light. Scholars writing on rape, violence against women, and elder abuse tend to analyze age and gendered sexual violence separately from each other, without accounting for their interplay. This Article proposes a conceptual framework of sexual abuse of older women that integrates age and gender in the analysis. To achieve this end, this Article examines 109 publicly available American cases involving sexual violence against women over the age of 60, between the years 2000 and 2018, which are based on a search of 1,308 American cases. Based on this new empirical database, this Article offers an opportunity for analyzing the social and legal “taboo” regarding sexual abuse of older women. Despite findings indicating that sexual abuse of older women (and older people in general) is a significant issue creating serious consequences for victims, the Article shows that legal actors, social workers, health professionals, family members, and society miss its signs. Sexual abuse of older women is being noticed and treated by the criminal justice system only when it reflects a “real rape” 1 scenario. The obstacles to effective prosecution and to full access to the criminal justice system are distinctive in the case of older victims because of the effect of age, the way age shapes the experience of older victims of sexual violence, the effects of sexual violence on the victims, and its interplay with gender. Although sexual violence against older women is a form of elder abuse, it should be viewed separately from other forms of elder abuse and should be understood as part of a wider context of gender-based violence. There is a need for a holistic approach to sexual violence of older women, which perceives the sexual violence as a unique phenomenon and provides older women with legal and social mechanisms that fit their needs and experience both as women and elderly people